'Mind will not mind' – Decoding consumers' green intention-green purchase behavior gap via moderated mediation effects of implementation intentions and self-efficacy. (10th January 2023) - Tawde, Swapnil; Kamath, Renuka; ShabbirHusain, R.V.
Abstract: Why do green consumers' purchase intentions often not convert into actual green buying actions? Within green attitude-intention-behavior research, the intention-behavior discord debate is under-researched. Limited research focuses on bridging this intention-behavior gap using consumers' intrapsychic traits (consumers' self-driven traits of psyche or personality). Using a dual-theory perspective, this study analyses whether implementation intentions and self-efficacy types can motivate green consumers to initiate their green actions. The proposed hypotheses are empirically validated using 674 green consumers using a structured questionnaire survey method. Further, Anchoring Vignettes Mechanism has been employed to improve data reliability and ward-off biases in survey measurement. The study decodes that when consumers are provided with cues for implementation intentions and self-efficacy, the combined effect results in motivating consumers toward green action initiation. The moderated-mediation analysis reveals an improved transition of green intentions to green behaviors with increased self-efficacy. The findings provide practical implications for encouraging green purchases. Highlights: Better understanding of green intention-behavior gap. Combination of implementation intentions and self-efficacy supports green actions. Highly self-efficacious individuals display stronger moderated-mediation effect. Using anchoring vignettes mechanism in green surveys does enhance data reliability.